2017
DOI: 10.1093/pcp/pcx014
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Jasmonic Acid-Associated Defenses by Thrips Alters Host Suitability for Conspecifics and Correlates with Increased Trichome Densities in Tomato

Abstract: Plant defenses inducible by herbivorous arthropods can determine performance of subsequent feeding herbivores. We investigated how infestation of tomato (Solanum lycopersicum) plants with the Western flower thrips (Frankliniella occidentalis) alters host plant suitability and foraging decisions of their conspecifics. We explored the role of delayed-induced jasmonic acid (JA)-mediated plant defense responses in thrips preference by using the tomato mutant def-1, impaired in JA biosynthesis. In particular, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
101
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 84 publications
(130 reference statements)
3
101
1
2
Order By: Relevance
“…pekinensis), JA is involved in defense against thrips (Abe et al 2008;Abe et al 2009). In tomato, the JA-signaling mutant, Defenceless1 (Def1), exhibits enhanced susceptibility to thrips feeding (Li et al 2002;Escobar-Bravo et al 2017) and a decline in thrips abundance was observed in tomato upon JA application in field conditions (Thaler et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…pekinensis), JA is involved in defense against thrips (Abe et al 2008;Abe et al 2009). In tomato, the JA-signaling mutant, Defenceless1 (Def1), exhibits enhanced susceptibility to thrips feeding (Li et al 2002;Escobar-Bravo et al 2017) and a decline in thrips abundance was observed in tomato upon JA application in field conditions (Thaler et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…When applied topically, jasmonate extracts have been shown to induce plant natural defense reactions . JA and its associated chemicals trigger signal transduction pathways that influence several genes to express encoding for defensive proteins …”
Section: Introductionmentioning
confidence: 99%
“…To deal with various threats, plants can activate defense mechanisms only when necessary. Such inducible defenses are triggered by wounding and insect attacks through jasmonate (JA) signaling (Mewis et al 2005; Escobar-Bravo et al 2017; Tsuda 2017; Zhu et al 2018; Zhou et al 2018; Nakano et al 2018), while constitutive defenses are continuously expressed.…”
Section: Introductionmentioning
confidence: 99%